2011
DOI: 10.1002/med.20249
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of Galectin‐9 in human disease

Abstract: In recent years, an important role has emerged for the glycan-binding protein Galectin-9 (Gal-9) in health and disease. In normal physiology, Gal-9 seems to be a pivotal modulator of T-cell immunity by inducing apoptosis in specific T-cell subpopulations. Because these T-cell populations are associated with autoimmunity, inflammatory disease, and graft rejection, it was postulated that application of exogenous Gal-9 may limit pathogenic T-cell activity. Indeed, treatment with recombinant Gal-9 ameliorates dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
127
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 109 publications
1
127
0
Order By: Relevance
“…Interestingly, Gal-9 has been tested as a potential therapeutic agent for various autoimmune diseases (7) and allergic diseases (8). Furthermore, it has been reported that Gal-9 suppresses the cell proliferation and tumor growth of various human cancer types (9,10), such as melanoma (11) and chronic myelogenous leukemia (12). We have previously shown that Gal-9 suppressed the cell proliferation and tumor growth of human hepatocellular carcinoma (HCC) and cholangiocarcinoma by inducing apoptosis, and we have identified several microRNAs (miRNAs) that are associated with the antitumor effect of Gal-9 (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Gal-9 has been tested as a potential therapeutic agent for various autoimmune diseases (7) and allergic diseases (8). Furthermore, it has been reported that Gal-9 suppresses the cell proliferation and tumor growth of various human cancer types (9,10), such as melanoma (11) and chronic myelogenous leukemia (12). We have previously shown that Gal-9 suppressed the cell proliferation and tumor growth of human hepatocellular carcinoma (HCC) and cholangiocarcinoma by inducing apoptosis, and we have identified several microRNAs (miRNAs) that are associated with the antitumor effect of Gal-9 (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Kadowaki T et al confirmed that Gal-9 signaling prolonged the survival of tumor-bearing mice (Kadowaki et al, 2012). In many solid cancers, the loss of Gal-9 expression is closely associated with metastatic progression (Wiersma et al, 2011). It was supposed that Gal-9 was involved in the suppression of tumor cell metastasis (Atsuya et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…T cell hemostasis, cell aggregation and metastasis is well known (14,15). Previous findings suggest that Gal-9 inhibits the proliferation of hematologic malignancies, including multiple myeloma (18) and chronic myeloid leukemia (19), and significantly retards the tumor growth of myeloma xenografts in mice (18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have uncovered additional mechanisms by which T cell immunoglobulin mucin-3, a receptor for Gal-9, negatively regulates T cell responses by promoting CD8+ T cell exhaustion and inducing the expansion of myeloid-derived suppressor cells (14,15 immunity by inducing a subset of macrophages and dendritic cells and activating tumor-specific CTLs and NK cells. Recombinant Gal-9 induced apoptosis in various T cell leukemic cell lines in a dose-dependent and functional CRD-dependent manner (16,17).…”
Section: Introductionmentioning
confidence: 99%